Innovation capacity in Mexican companies: mediation in the relationship orientation to learning-business performance - Demuner Flores, María del Rosario (Acta Universitaria, 2021)
Innovation helps to deal with turbulent environments. Strategically combining its dynamism with knowledge as its antecedent will intensify performance. The objective was to analyze relationships between learning orientation, innovation capacity and business performance, as well as to analyze innovation capacity as a mediator between learning orientation and performance in Mexican companies. Structural equation modeling (PLS-SEM) was calculated, suggesting that empowering learning promotes innovation and improves business performance, and that strategically managing innovation capacity directly and indirectly influences performance. Results encourage companies to opt for knowledge to promote the development of innovation and enjoy its benefits. They provide insight to institutions interested in business competitiveness to promote scientific and technological progress. The study also contributes to the understanding of the mediating effect caused by innovation.